Analysis of purified human liver alpha-L-fucosidase by western-blotting with lectins and polyclonal and monoclonal antibodies. - Johnson, S W (1992)
Western-blot analysis [with lectins, polyclonal antibodies (pAbs) and four monoclonal antibodies (mAbs)] was employed to investigate the structural relationship between the separated isoforms and subunits of purified human liver alpha-L-fucosidase. SDS/PAGE and Western-blot analysis indicated the presence of two protein bands of 51 kDa and 56 kDa that were recognized by the pAbs. Polyacrylamide-gel isoelectric focusing (PAG-IEF) followed by blotting indicated that the pAbs and mAbs recognized at least five fucosidase isoforms (pI values 3.6-6.0). Lectin blotting indicated an enrichment of sialic acid residues in the more acidic isoforms. Western-blot analysis indicated that four mAbs recognized the 51 kDa subunit and at least two mAbs recognized the 56 kDa subunit. The subunit composition of the isoforms (separated by PAG-IEF) of human liver alpha-L-fucosidase was investigated by SDS/PAGE. One or two closely spaced bands were found for each isoform with a trend of increasing relative amounts of the high-molecular-mass band in the more acidic isoforms relative to the more neutral isoforms. Neuraminidase treatment of alpha-L-fucosidase resulted in a decrease in the amount of the high-molecular-mass subunit and an increase in the amount of the low-molecular-mass subunit, suggesting that these subunits are related at least in part by sialic acid residues. In addition, blotting with lectins indicated the presence of sialic acid residues only in the high-molecular-mass subunit. N-Glycanase treatment led to the disappearance of the glycosylated 56 kDa and 51 kDa protein bands and the appearance of non-glycosylated protein bands at 48 kDa and 45 kDa. The overall results indicate that (1) N-glycosylation contributes to, but does not account completely for, structural differences in the fucosidase subunits and (2) the more acidic isoforms of fucosidase contain enriched relative amounts of the sialylated high-molecular-mass subunit.